A phase III, multicenter randomized controlled trial of neo-adjuvant chemotherapy paclitaxel plus cisplatin versus surgery alone for stage IIA–IIIB esophageal squamous cell carcinoma - Zheng, Yan; Li, Yin; Liu, Xianben; Zhang, Ruixiang; Wang, Zongfei; Sun, Haibo; Liu, Shilei (Journal of Thoracic Disease; Vol 9, No 1 (January 24, 2017): Journal of Thoracic Disease, 2017)
Background: The survival benefits of neoadjuvant chemotherapy (NAC) for esophagus squamous cell carcinoma (ESCC) remains controversial. The surgical procedure was not well defined in NAC strategy, in past trials. The different surgical procedure and different levels of lymphadenectomy may decrease the survival benefits from NAC. The new chemotherapy regimen with paclitaxel is promising. The purpose of this study is to confirm the superiority of paclitaxel, cisplatin and McKeown esophagectomy with total two-field lymphadenectomy compared with surgery alone for ESCC. Methods: A two-arm phase III trial was launched in June 2015. A total of 528 patients will be recruited from eight Chinese institutions within 2.5 years. The overall survival (OS) is the primary endpoint, and the secondary endpoints include disease-free survival (DFS), R0 resection rate, complication rate, perioperation mortality, days of hospitalization, quality of life (QOL), NAC response rate, pathologic response rate, toxicities of NAC, prognostic factors, predictive factors, progression-free survival (PFS), and adverse events. Discussion: The study will provide the final conclusion of NAC for ESCC in China. Trial registration: NCT02442440 (https://register.clinicaltrials.gov/).